What Competencies Do project Managers Need? - Mahmood, Assoc.Prof.Dr.Abdullah; M.A.Hamidaddin, Abdulkareem; Mohd Shafiei, Dr.Mohd Wira (2006)
Professionals such as Architects, Civil Engineers and Quantity Surveyors are the main providers of project management services in the construction industry.